Human Lice: Body Louse, Pediculus humanus humanus Linnaeus and Head Louse, Pediculus humanus capitis De Geer (Insecta: Phthiraptera (Anoplura): Pediculidae) - H. V. Weems, Jr.; Thomas R. Fasulo (EDIS)
This document is EENY-104, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 1999. Reviewed May 2003.